Growing self-assisted GaAs nanowires up to 80 μm long by molecular beam epitaxy. (22nd January 2023) - Becdelievre, Jeanne; Guan, Xin; Dudko, I; Regreny, Philippe; Chauvin, Nicolas; Patriarche, Gilles; Gendry, Michel; Danescu, Alexandre; Penuelas, José
Abstract: Ultralong GaAs nanowires were grown by molecular beam epitaxy using the vapor–liquid–solid method. In this ultralong regime we show the existence of two features concerning the growth kinetic and the structural properties. Firstly, we observed a non-classical growth mode, where the axial growth rate is attenuated. Secondly, we observed structural defects at the surface of Wurtzite segments located at the bottom part of the nanowires. We explain these two phenomena as arising from a particular pathway of the group V species, specific to ultralong nanowires. Finally, the optical properties of such ultralong nanowires are studied by photoluminescence experiments.